STUDI PERHITUNGAN STRUKTUR DINDING PENAHAN TANAH PADA LONGSORAN JALAN LOA JANAN STA.0+035 – STS.0+090 KECAMATAN LOA JANAN KABUPATEN KUTAI KARTANEGARA - UDDIN, SAHAR (KURVA S JURNAL MAHASISWA, 2014)
What is meant by a landslide is the movement of a land mass slopes downward slopestability due to the disruption of the amount of soil moved it apart from its geometric depends on theseverity and also from the shear strength (shear strength). Shear strength is not fixed, and can bedecreased due to increasing water content in the soil itself, in addition to the influence of otherdisorders. Disruption to the stability of the slope can be caused by nature and also by humanactivity itself. The first so-called natural disasters, which can be caused by earthquakes or by heavyrain is prolonged, the second is human error, and generally in the form of imposition of excessive(overloading), excavation uncontrolled, drainage is less than perfect, and deforestation.Loa thorn road is one of the areas that has undulating topography. Wave in question is thenatural state of hills and valleys, this has resulted in some segments of roads should be on theslopes. The presence of natural factors, especially rain and ground water flow that makes it loseground slope stability or ability to withstand sliding friction that occurs, automatically highwayabove it will be impaired and will also affect the level of service. So that public facilities canfunction optimally we need to hold the handling of an avalanche is one of them by making theconstruction of retaining soil so that the soil in these segments do not move or shift.From the results of calculations can be concluded that, the dimensions of retaining wall is 3 metershigh and 2.5 meters wide, 0.40 meters thick plate with a length of 55 meters, retaining wall stabilitysafe to bolster however affect the shear, so it is necessary to pile foundation meperkaku wallstructure and pile foundation.